\(A=\left(\frac{1}{5}\right)^1+\left(\frac{1}{5}\right)^{^2}+...+\left(\frac{1}{5}\right)^{2015}\)
\(A=\frac{1}{5}+\frac{1}{5^2}+...+\frac{1}{5^{2015}}\)
\(5A=5\left(\frac{1}{5}+\frac{1}{5^2}+...+\frac{1}{5^{2015}}\right)\)
\(5A=1+\frac{1}{5}+\frac{1}{5^2}+...+\frac{1}{5^{2014}}\)
\(\Rightarrow5A-A=\left(1+\frac{1}{5}+\frac{1}{5^2}+...+\frac{1}{5^{2014}}\right)-\left(\frac{1}{5}+\frac{1}{5^2}+...+\frac{1}{5^{2015}}\right)\)
\(\Rightarrow4A=1-\frac{1}{5^{2015}}\)
\(\Rightarrow A=\frac{1-\frac{1}{5^{2015}}}{4}\)
Vì \(1-\frac{1}{5^{2015}}